2022
DOI: 10.1002/pon.6060
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of long‐term childhood acute lymphoblastic leukemia survivors: Comparison with healthy controls

Abstract: Objective: Improved treatment landscape has led to better outcomes for paediatric acute lymphoblastic leukemia (ALL) survivors. As the number of survivors increase, we need to elucidate the long-term quality of life (QoL) and domains of complaints in these patients. Furthermore, the main priorities of these patients need to be clarified. We assessed long-term QoL outcomes of survivors of childhood ALL compared to matched population controls.Methods: QoL data were collected from survivors recruited in France an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Of the 23 studies that found a lower QoL in survivors, 12 were based on survivors of various cancers, 20‐25,28,31‐35 six on survivors of haematological cancers, 37‐39,44,46,48 three on brain tumour survivors, 49,51,52 one on survivors of differentiated thyroid carcinoma 53 and one on survivors of head‐and‐neck rhabdomyosarcoma 54 . The five studies that found a higher QoL in survivors were based mainly on survivors of haematological cancers 19,40,42,43,45 . One of the three studies that found no difference in QoL was based on brain tumour survivors, 50 while the other two were based on survivors of various cancers 30,36 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 23 studies that found a lower QoL in survivors, 12 were based on survivors of various cancers, 20‐25,28,31‐35 six on survivors of haematological cancers, 37‐39,44,46,48 three on brain tumour survivors, 49,51,52 one on survivors of differentiated thyroid carcinoma 53 and one on survivors of head‐and‐neck rhabdomyosarcoma 54 . The five studies that found a higher QoL in survivors were based mainly on survivors of haematological cancers 19,40,42,43,45 . One of the three studies that found no difference in QoL was based on brain tumour survivors, 50 while the other two were based on survivors of various cancers 30,36 …”
Section: Resultsmentioning
confidence: 99%
“…The included articles provided data on a total of 14 342 survivors of childhood cancer. Three articles were based on data from a French cohort of survivors of leukaemia, [37][38][39] two articles were from studies in northern Italy, 19,20 two articles were based on data from a Belgian and French cohort of survivors of hematologic cancers 40,41 and five articles used data from the Dutch LATER registry, [21][22][23][24][25] with overlapping populations. All articles were screened for overlapping populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations